Ameliorated chest drain wound closure in patients undergoing uniportal thoracoscopic pulmonary resection - Chou, Ping-Ruey; Kao, Chieh-Ni; Lo, Yu-Ting; Chuang, Che-Yu; Liu, Yu-Wei (Frontiers in Surgery, 2023)
Background: Although uniportal video-assisted thoracoscopic surgery (VATS) has been performed for a wide array of thoracic diseases, unsightliness and poor wound healing often occur, particularly when a chest drain is placed postoperatively. Different chest drain wound closure (CWC) methods have been introduced with the benefits of cosmesis and patient satisfaction. We aimed to describe our improved CWC technique in this setting and assess its efficacy.Methods: A total of consecutive 334 patients undergoing uniportal VATS pulmonary resection with single chest drain placement were investigated from 2016 to 2021. The techniques for CWC were classified into the conventional method (35 patients, group A), continuous suture with removal-free stitches (122 patients, group B), and continuous suture with removal-free barbed suture plus topical skin adhesives (177 patients, group C).Perioperative data and complications related to CWC were analyzed.Results: Group C had a significantly shorter operative time, postoperative hospital stay, and chest tube days than groups A and B (all p < 0.01). In terms of chest tube-related complications, there were no statistically significant differences in post-removal pneumothorax, subcutaneous emphysema, incisional effusion leakage, wound dehiscence, or infection. Overall, significant differences in scar scale scores were observed between the groups, where the ameliorated group C was superior to the conventional group A (p < 0.01).The improved CWC technique using continuous sutures with removal-free barbed sutures and topical skin adhesives is simple, safe, and effective. This may be a favorable CWC strategy when performing uniportal VATS, with enhanced patient satisfaction.